EXPERIMENTAL EVALUATION OF STEREOLOGICAL METHODS FOR DETERMINING 3D GRAIN SIZE AND TOPOLOGICAL DISTRIBUTIONS - Liu, Guoquan; Yu, Haibo (Image Analysis and Stereology, 2011)
The conventional serial sectioning analysis and a set of modern stereological methods, including disector, selector, point-sampled intercepts, point-sampled area, and their combinations, have been used in this paper to measure the grain size, grain size distribution, topological parameters and their distributions in a spacefilling single-phase grain structure of steel. The results from different methods are compared and used to evaluate the methods quantitatively, based on which some suggestions will be given for selection of experimental methods in materials stereology research.